2020
DOI: 10.2981/wlb.00649
|View full text |Cite
|
Sign up to set email alerts
|

Consequences of ignoring group association in spatial capture–recapture analysis

Abstract: BioOne Complete (complete.BioOne.org) is a full-text database of 200 subscribed and open-access titles in the biological, ecological, and environmental sciences published by nonprofit societies, associations, museums, institutions, and presses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
90
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(97 citation statements)
references
References 36 publications
7
90
0
Order By: Relevance
“…Different sources of heterogeneity can bias noninvasive genetic population density estimates, e.g. sex, age class, social status, individual differences in behaviour or space use (Boulanger et al 2004;Bischof et al 2020). Furthermore, differences in defecation rates can result in heterogeneous detection probabilities (Marucco et al 2009;Lunt & Mhlanga 2011), an aspect that in our opinion should be addressed in future studies.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Different sources of heterogeneity can bias noninvasive genetic population density estimates, e.g. sex, age class, social status, individual differences in behaviour or space use (Boulanger et al 2004;Bischof et al 2020). Furthermore, differences in defecation rates can result in heterogeneous detection probabilities (Marucco et al 2009;Lunt & Mhlanga 2011), an aspect that in our opinion should be addressed in future studies.…”
Section: Discussionmentioning
confidence: 94%
“…In contrast, adult stags live solitary or in bachelor herds most of the year and therefore potentially show a different space use compared to the juvenile and subadult males. This aspect could introduce bias (Hickey & Sollmann 2018;Bischof et al 2020) that would not be accounted for by sex-specific estimation of population density. Further research, e.g.…”
Section: Discussionmentioning
confidence: 99%
“…(2017) were unsure to what extent the measures of uncertainty in their study of a community western chimpanzees ( Pan troglodytes verus ) were underestimated. Bischof, Dupont, Milleret, Chipperfield, and Royle (2020) found that SCR models are robust to moderate levels of aggregation and cohesion, with low to moderate aggregation and cohesion not impacting the bias and precision of density and σ estimates. Inferences from SCR density estimates for species with small group sizes can be trusted even if grouping is ignored (Bischof et al., 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Bischof, Dupont, Milleret, Chipperfield, and Royle (2020) found that SCR models are robust to moderate levels of aggregation and cohesion, with low to moderate aggregation and cohesion not impacting the bias and precision of density and σ estimates. Inferences from SCR density estimates for species with small group sizes can be trusted even if grouping is ignored (Bischof et al., 2020). Although the fission–fusion social structure of caribou leads to frequent exchanges of individuals between groups, boreal caribou were rarely resampled together as a group or as a pair in our study (unpublished data).…”
Section: Discussionmentioning
confidence: 99%
“…However, misspecifications may have consequences for estimates of other important parameters besides density/population size, such as home range area, habitat use/selection, movement, and connectivity, all of which feature increasingly in the SCR literature (Efford et al, 2016; Royle et al, 2013b; Gardner et al, 2018; Royle et al, 2013a). Furthermore, even in the absence of systematic bias, misspecifications could impact the confidence one can place in those estimates by affecting the associated precision and coverage probability (Bischof et al, 2020a).…”
Section: Introductionmentioning
confidence: 99%